An honorable mirror for the youth of Spain: About an underappreciated treatise by Isidore of Seville and its translation into Russian : A review of: Vorontsov, S. A., Birkin, M. Yu., Marei, E. S., Chernin, L. V., & Volkov, A. A. (Eds.). Isidor Sevil’skii. O tserkovnykh sluzhbakh [Isidore of Seville. On Church Duties]. Nauka. 343 p. (In Russian) - I. M. Nikolsky (Шаги)
Нет аннотации